Case report: photo‐onycholysis after PUVA treatment for hypopigmented mycosis fungoides with response to topical steroid - Tern, Paul Jie Wen (Clin Case Rep, 2017)
Melanin in the nail bed in patients with skin type VI has been suggested to afford some protection against photo‐onycholysis. We report a case of a 16‐year‐old male patient with skin type VI with onycholysis following PUVA treatment for hypopigmented mycosis fungoides. Symptoms resolved with the application of topical steroid.